Digital Twin Platforms: Requirements, Capabilities, and Future Prospects - Lehner, Daniel; Pfeiffer, Jerome; Tinsel, Erik-Felix; Strljic, Matthias Milan; Sint, Sabine; Vierhauser, Michael; Wortmann, Andreas; Wimmer, Manuel (IEEE software, 2022)
Digital twins (DTs) have emerged as a paradigm for the virtual representation of complex systems alongside their underlying hardware. We investigate the benefits of Amazon, Eclipse, and Microsoft DT platforms and assess the extent to which they meet standard requirements.